دليل حول تقنيات تكاثر و إكثار الخروب في تونس - El Khorchani, Ali; Elhaj, Ammar; MEZNI, Faten; Slama, Awatef; Ayari, Faten; Bessouda, Balkiss; Kortas, Ghada; Belkhir, Amira; Jean, Edouard; Khaldi, Abdelhamid (Association les Amis de Capte (LACT) & Institut de Recherches en Génie Rural, Eaux, et Forets (INRGREF), 2024)
يقدم هذا الكتيب وصفاً نباتياً وبيئياً لزراعة الخروب، بالإضافة إلى الممارسات التقنية والمعلومات للمزارعين حول كيفية زراعته وتكاثره وإكثاره في تونس ----------------------------------------- This guide provides a botanic and ecological description of the Carob plant, as well as technical practices and information to farmers on how to cultivate, reproduce, and multiply it in Tunisia. With this guide, aimed at farmers, foresters and private individuals, the Association les Amis de CAPTE (LACT) and the Institut National de la Recherche du Génie Rural des Eaux et Forêts (INRGREF) are seeking to speed up the development of carob-based agroforestry systems in Tunisia.